Evaluation of the Influence of Pre-treatment Temperature of Leucaena leucocephala in the Biosorption of 5G Blue Dye - Perin, Matheus José; Giacobbo, Heloíse Angélica; Suzaki, Pedro Yahico Ramos; Johann, Gracielle (Orbital: The Electronic Journal of Chemistry, 2019)
Leucaena leucocephala is an invasive exotic tree plant, and because of these characteristics, it becomes an environmental problem. In this sense, the main objective of the present study was to evaluate the adsorption capacity of 5G blue dye, using dry L. leucocephala leaves under different temperatures. Drying kinetic, centesimal composition and micrographs after drying of the leaves were also evaluated. For drying, the Valcan model best described the process kinetics, presenting a correlation coefficient of 99.4% and an average error of 1.41%. For the centesimal composition, 3.9% of moisture, 7.5% of ash, 23.8% of crude protein, 29.5% of crude fiber, 3.9% of ethereal stratum and 31.4% of soluble carbohydrate were obtained. In the evaluation of the adsorptive capacity, the temperature of 40 °C was the one that produced the largest adsorbed amount of dye mass/leaf mass, 9.4 mg g-1. The qualitative results obtained agreed with the one observed in the micrographs, so that the leaves of L. leucocephala have, therefore, industrial application with biosorbent.DOI: http://dx.doi.org/10.17807/orbital.v11i6.1266